Internationalization of Higher Education: Case Studies of Thailand and Malaysia - Armstrong, Napaporn; Laksana, Sangob (Scholar: Human Sciences, 2016)
Internationalization of Higher Education has grown considerably as a topic for several different reasons as for instance, a desire to promote mutual understanding, the migration of skilled workers in a globalized economy, the desire of institutions to generate additional revenues or the need to build a more educated work-force in the home countries which are generally emerging economies (OECD, 2004). Moreover the impact of ASEAN Communities which will be implemented at the end of 2015 supports the development of internationalization of higher education in Thailand to being into a very significant area that should be considered as an important agenda item at the level of ASEAN. This article aims to present the findings of the study on internationalization of higher education from the case studies of Thailand (Assumption University in Thailand) and Malaysia (International Islamic University Malaysia) which are ASEAN member countries. The objectives of this study are: to explore critical components of internationalization in higher education, to identify the factors that effectively enhance the achievement of internationalization in higher education from case studies in Thailand and Malaysia and to create then validate a best practice model of internationalization for higher education in Thailand. This study uses a mixed method of qualitative and quantitative. Data is collected by interviewing key people from the government and case studies in universities of both countries together with questionnaires directed to experts and experienced practitioners relating to internationalization and including focus group of selected experts on higher education and internationalization. This data is then brought together where the findings identified the critical components of internationalization in higher education and the factors that effectively enhance the achievement of internationalization in higher education from case studies in Thailand and Malaysia and after this, then a best practice model of internationalization for higher education in Thailand was created and validated. The model comprises seven key components: the first three components are in the public sector which are government, the Higher Education Commission and the Office of Higher Education Commission, the fourth is higher education institutions which have six quality elements inside, the fifth is international network/partner, the sixth is employers and the seventh is the bodies or agencies related to quality enhancement.